Austenitic stainless steel for connector and preparation method thereof
By controlling the element composition and processing technology in austenitic stainless steel, the problem of insufficient strength and elongation of the connecting member materials in the prior art is solved, and high-strength, high-elongation and low-cost austenitic stainless steel preparation is achieved, which is suitable for the manufacture of connecting parts in the automobile, pipeline, food and medical industries.
Patent Information
- Application Number
- CN202310307143.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-27
AI Technical Summary
When manufacturing connectors, it is difficult for the existing austenitic stainless steel to meet the requirements of high yield strength, tensile strength and high elongation at the same time, and it is costly and has insufficient corrosion resistance.
By controlling the content of elements such as C, Si, Mn, Cr, Ni, N, Cu, Mo, etc., it is ensured that Creq≥18%, Nieq≥12%, Md30<0, and high-temperature ferrite content δ≤3%. Multiple passage cold rolling and annealing treatment are used to form stable austenite structure and improve work hardening efficiency.
The yield strength is 410~480MPa, tensile strength is 650~800MPa, and the elongation is greater than 40%. At the same time, the cost of using precious elements is reduced, and the corrosion resistance and plastic toughness of the material are improved.
Smart Images

Figure BDA0004147211410000071
Abstract
Description
Technical Field
[0001] The invention relates to low-cost austenitic stainless steel and a preparation method thereof, which are mainly used for manufacturing connectors in industries such as automobiles, pipelines, food and medical treatment. Background Art
[0002] The stainless steel used to make connectors must have good plasticity and corrosion resistance, especially the connector clamp must undergo large plastic deformation to ensure the tightness of the connection. The materials currently used to make connectors are austenitic stainless steel 304 and hot-dip galvanized high-strength steel. 304 stainless steel has good corrosion resistance, good plasticity, and an elongation generally higher than 40%, but low yield strength, generally lower than 300MPa. Moreover, 304 stainless steel contains more than 8% Ni, which is more expensive. The cost of hot-dip galvanized high-strength steel used to make connectors is lower than that of 304 stainless steel, but the yield strength is generally 380-480MPa, and the elongation is less than 20%. Therefore, compared with austenitic stainless steel 304, hot-dip galvanized high-strength steel has higher strength, but lower plasticity and toughness, and cannot meet the high yield strength and high elongation at the same time. In addition, the corrosion resistance of hot-dip galvanizing depends on the quality of the coating. If the coating is defective, the substrate will corrode quickly, causing the connector to fail.
[0003] To this end, for example, the Chinese invention patent "A high-strength nitrogen-containing economical austenitic stainless steel and its manufacturing method", whose patent number is ZL201711225914.8 (authorization publication number is CN109837470B) discloses a high-strength nitrogen-containing economical austenitic stainless steel, the chemical composition weight percentage of which is: C: 0.05-0.15%, Si: 0.3-1%, Mn: 8.5-11.0%, Cr: 14.0-16.0%, Ni: 1.0-2.5%, N: 0.10-0.25%, P<0.08%, S<0.01%, Cu: 0.5-2.0%, Mo: 0.1-0.5%, the rest is Fe and unavoidable impurities, and Md 30 / 50 ≥20℃. Yield strength ≥650MPa, tensile strength ≥1000MPa, elongation ≥35%, but due to Md 30 / 50 ≥20℃, there is deformation when making the connecting parts, which is very likely to produce a large amount of deformation martensite. The strength is increased after deformation, but it will cause delayed cracking and reduce the service life of the connecting parts.
[0004] Another example is the Chinese invention patent application "Austenitic Stainless Steel", whose patent application number is CN201910070342.3 (application publication number is CN109913747A) discloses austenitic stainless steel, which contains less than 0.03% carbon (C), 0.2-0.6% silicon (Si), 1.0-2.0% manganese (Mn), 19.0-21.0% chromium (Cr), 7.5-9.5% nickel (Ni), 0.4-1.4% molybdenum (Mo), less than 1.0% copper (Cu), 0.10-0.25% nitrogen (N), optionally less than 1.0% cobalt (Co), optionally less than 0.006% boron (B), and the rest is iron (Fe) and occasional impurities. The steel has a guaranteed strength Rp 0.2 320-450MPa and guaranteed strength Rp 1.0 370-500MPa, and tensile strength R m The pitting resistance equivalent number (PREN) is greater than 24, and the austenitic stainless steel has an Md of less than -80 °C. 30 Temperature, here Md 30 =551-462x(%C+%N)–9.2x%Si–8.1x%Mn–13.7x%Cr-29x(%Ni+%Cu)–18.5x%Mo-68x%Nb. This patent contains high content of precious alloy elements Cr, Ni and Mo, and may also contain Co. It not only increases the cost, but also increases the stacking fault energy of the material. Metal materials with high stacking fault energy are prone to cross-slip dislocations during cold deformation, which reduces the dislocation increment rate and is not conducive to improving strength through work hardening.
[0005] For example, the austenitic stainless steel disclosed in "Corrosion-resistant low-component austenitic stainless steel" with application number CN200880121552.0 (application publication number CN101903549A) contains, by weight%, up to 0.20C, 2.0-6.0Mn, up to 2.0Si, 16.0-23.0Cr, 5.0-7.0Ni, up to 3.0Mo, up to 3.0Cu, 0.1-0.35N, up to 4.0W, up to 0.01B, up to 1.0Co, iron and impurities. The austenitic stainless steel has a ferrite number of less than 11, MD 30The value is less than -10℃. The difference between this patent and the present application is that the patent contains up to 4.0W, up to 0.01B, up to 1.0Co, a yield strength of 52.2-59.3ksi, a tensile strength of 105-111.1ksi, and an elongation of 32%-42%. Converted into international units: yield strength 360-409MPa, tensile strength 727-766MPa, and elongation 32%-42%. This patent uses a combination of elements Mn, Cu and N to replace Ni and Mo to prepare corrosion resistance, formability and other properties comparable to or better than some high-nickel-molybdenum alloys. The goal is to reduce costs and achieve the performance of high-nickel-molybdenum alloys. However, compared with 304 stainless steel, it still has a higher cost, and its mechanical properties cannot meet the specific requirements of connectors, such as yield strength Rp0.2 of 410-480MPa, tensile strength Rm of 650-800MPa, and elongation A greater than 40%.
[0006] Austenitic stainless steel disclosed in "Poor Austenitic Stainless Steel" with application number CN201080056955.9 (application publication number CN102695815A) contains, which contains relatively low nickel and molybdenum content, and exhibits corrosion resistance, high temperature deformation resistance and formability comparable to certain alloys containing higher nickel and molybdenum content. The embodiment of austenitic stainless steel contains, by weight %, up to 0.20 carbon, 2.0-9.0 manganese, up to 2.0 silicon, 15.0-23.0 chromium, 1.0-9.5 nickel, up to 3.0 molybdenum, up to 3.0 copper, 0.05-0.35 nitrogen, (7.5 (% carbon)) ≤ (% niobium + % titanium + % vanadium + % tantalum + % zirconium) ≤ 1.5, iron and occasional impurities. The yield strength obtained is 46.1-53.7 ksi, the tensile strength is 102-106.4 ksi, and the elongation is 41-49%. The patent uses economical elements to achieve the corrosion resistance, strength and hardness of titanium-containing austenitic stainless steel, and its composition range is very wide, wider than the standard composition of stainless steel, and has almost no guiding significance for practical application. Judging from the performance published in the examples, for example, the yield strength is 43.4-50.1 ksi, and the tensile strength is 90.2-118.2 ksi, which are converted into international units of 299-345 MPa and 621-814 MPa, respectively, which do not meet the yield strength requirements of stainless steel for connectors.
[0007] Therefore, it is necessary to further improve the existing stainless steel. Summary of the invention
[0008] The first technical problem to be solved by the present invention is to provide an austenitic stainless steel for connectors which has high yield strength and tensile strength while maintaining an elongation of more than 46% in view of the current status of the above-mentioned prior art.
[0009] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned austenitic stainless steel.
[0010] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: an austenitic stainless steel for a connector, characterized in that it includes the following components by mass percentage: C: 0.04-0.06%, Si: <1.0%, Mn: 3.0-4.0%, Cr: 17.0-18.0%, Ni: 5.0-6.0%, N: 0.15-0.25%, Cu: 2.0-3.0%, Mo: 0.2-0.6%, P: ≤0.040%, S: ≤0.030%, and the rest are Fe and unavoidable impurity elements, while satisfying Creq≥18%, Nieq≥12%, Mdeq≥10%. 30 <0 and high temperature ferrite content δ: 0<δ≤3%, where Creq=%Cr+1.5*%Si+%Mo, Nieq=%Ni+30*(%C+%N)+0.5*%Mn, Md 30 (℃)=551-462(%C+%N)-9.2*%Si-8.1*%Mn-13.7*%Cr-29*%Ni-18.5*%Mo-29*%C u; δ=((%Cr+%Mo+1.5*%Si+18) / (Ni+30*(%C+%N)+0.5*%Mn+36)-0.738)*166.7.
[0011] Among the above austenitic stainless steels:
[0012] C is a strong austenite forming element and can significantly improve the strength of steel through solid solution strengthening. However, carbon easily forms high-chromium Cr in the temperature range of 400-700℃. 23 C6 carbides precipitate at the grain boundaries, resulting in chromium-poor areas near the grain boundaries, which ultimately leads to a decrease in the intergranular corrosion resistance of the steel. Therefore, C should be defined as 0.04-0.06%.
[0013] Si is a commonly used deoxidizing element. Si dissolved in the matrix increases the intergranular corrosion sensitivity and strength of steel. Therefore, the Si content is defined as <1.0%.
[0014] Mn is an austenite-forming element and strongly stabilizes austenite, which can increase the strength of steel and improve its hot plasticity. Properly increasing the Mn content will compensate for the problem of decreased austenite stability caused by reduced nickel content, so Mn is defined as 3.0-4.0%.
[0015] Cr is an element that strongly forms and stabilizes ferrite, shrinks the austenite zone, and forms a passivation film of chromium oxide with oxygen at room temperature, making the steel stainless. Chromium improves the steel's ability to resist oxidizing media and acidic chloride media, but excessive Cr will cause the brittleness of stainless steel. Therefore, Cr is defined as 17.0-18.0%.
[0016] Ni is an element that strongly forms and stabilizes austenite and expands the austenite phase. As the nickel content increases, the plasticity and toughness of the steel improves, but the nickel content has a greater impact on the manufacturing cost, so Ni is defined as 5.0-6.0%.
[0017] Nitrogen is a strong austenite-forming element. As an interstitial atom, it can improve the strength of austenitic stainless steel through solid solution strengthening. However, excessive nitrogen content is easy to form precipitates with chromium, reducing the cold and hot processing properties of steel. Depending on the content of other elements, the appropriate nitrogen content is 0.15-0.25%.
[0018] Cu is an austenite forming element, which is beneficial to the solid solution of nitrogen and improves the plasticity and deep drawing properties of steel at room temperature. Therefore, Cu is defined as 2.0-3.0%.
[0019] Mo is a ferrite-forming element, which is beneficial to improving pitting corrosion resistance. However, too high Mo content will increase costs. Therefore, Mo is defined as 0.2-0.6%.
[0020] P and S are both unavoidable impurity elements, but have an adverse effect on performance and should be less than 0.04 mass % and 0.005 % respectively.
[0021] Creq≥18%, Nieq≥12% ensures an austenitic structure at room temperature. If Creq<18%, there will be a certain amount of martensite in the structure at room temperature. Martensite can increase strength but reduce plasticity, and is prone to cracking when used as a connecting piece.
[0022] The austenitic stainless steel has a yield strength of 410-480 MPa, a tensile strength of 650-800 MPa, and an elongation greater than 40%.
[0023] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing austenitic stainless steel for the connecting piece, characterized in that it includes the following steps in sequence:
[0024] 1) Smelting: The molten steel is smelted into molten steel in the furnace according to the above composition ratio, and then the molten steel is poured into the baked ladle and hoisted to the refining station for refining. Microalloying is performed during refining to ensure that the composition meets Md 30 <0 and δ<2, then feed the boron wire and the silicon-calcium wire to ensure that the molten steel composition meets the above requirements, and then obtain the slab or billet through continuous casting;
[0025] 2) hot rolling and annealing: hot rolling and annealing the slab or billet in step 1);
[0026] 3) Cold rolling: cold rolling the product of step 2);
[0027] 4) Annealing and pickling: The cold rolled product is annealed and pickled to remove the iron oxide scale on the surface.
[0028] Preferably, after step 4), flattening and adjusting rolling is performed to obtain a flat steel plate. In this way, a steel plate with a desired flatness can be obtained.
[0029] Preferably, the elongation of the flattening is 2% to 4%, and the flattening is performed in 3 to 11 passes. The flattening with small deformation and multiple passes can increase the dislocation accumulation rate of the prepared material, improve the work hardening effect of the prepared material, and improve the strength through work hardening.
[0030] In step 1), feed boron wire and calcium silicate wire, and ensure the sedation time of soft stirring is ≥ 15 minutes.
[0031] Preferably, in step 2), the heating temperature is 1180-1240°C, and the annealing temperature is 1080-1120°C.
[0032] Further preferably, in step 3), the total cold rolling reduction is ≥50%, the reduction in each pass is 8% to 12%, and the target thickness after cold rolling is 1.0 mm to 1.2 mm. A total reduction rate of ≥50% ensures the accumulation of sufficient deformation energy, increases the nucleation points and nucleation rate of grains in the subsequent annealing process, and refines the grain size after annealing; a total reduction rate of ≥50% can also reduce the roughness of the surface of the prepared product to meet the roughness requirements of stainless steel for connectors. Limiting the pass reduction rate is conducive to the accumulation of deformation energy storage, increasing the power of grain recrystallization in subsequent annealing, and achieving the purpose of refining grains and improving strength.
[0033] Preferably, in step 2), the target thickness after hot rolling is 2 mm to 3.5 mm, and the annealing temperature is 1080° C. to 1120° C. The finished thickness of the connector is generally 1.0 mm to 1.2 mm. To ensure that the total cold rolling reduction is ≥ 50%, the target thickness of hot rolling is preferably 2 mm to 3.5 mm. The annealing temperature is 1080° C. to ensure that all carbides produced during hot rolling are dissolved in the matrix, avoiding the formation of chromium-poor areas around the grain boundaries due to the precipitation of carbides.
[0034] Preferably, in step 4), the annealing temperature is 1060-1070°C.
[0035] Compared with the prior art, the advantages of the present invention are: the austenitic stainless steel is mainly ensured to be a stable austenite phase at room temperature by coordinating the elements and contents of C, Si, Mn, Cr, Ni, N, Cu, Mo, etc., mainly by reducing the content of the precious element nickel and increasing the content of nitrogen and manganese, but the performance of the stable austenite, especially the yield strength, is low and it is difficult to reach more than 410MPa. The general method for austenitic stainless steel to obtain a yield strength greater than 410MPa is to make the structure at room temperature metastable. Metastable austenitic stainless steel produces a certain amount of deformation martensite through deformation to improve strength. Because the deformation martensite and the austenite phase are two phases, it is easy to cause aging cracking during service. The present invention adopts C: 0.04-0.06%, Si: <1.0%, Mn: 3.0-4.0%, Cr: 17.0-18.0%, Ni: 5.0-6.0%, N: 0.15-0.25%, Cu: 2.0-3.0%, Mo: 0.2-0.6%, P: ≤0.040%, S: ≤0.030%, and the rest is Fe and inevitable impurity elements, so that austenitic stainless steel produces 0-3% high-temperature ferrite during the solidification process. The high-temperature ferrite precipitated first reduces the Cr content in the austenite phase, reduces the stacking fault energy of the material, and increases the dislocation multiplication rate. Creq ≥ 18%, Nieq ≥ 12% ensures that it is an austenite structure at room temperature, and Nieq ≥ 12% ensures that the ferrite phase precipitated first during high-temperature solidification can be transformed into the austenite phase as the solidification temperature decreases, ensuring that the ferrite phase at room temperature is within a certain range. At the same time, Md 30 Less than 0 ensures that no phase change occurs after a certain amount of cold deformation, and only the work hardening of the austenite phase, i.e., dislocation accumulation, occurs during deformation. At the same time, the dislocation multiplication rate is increased by controlling the rate of cold deformation to improve the work hardening efficiency, thereby ensuring that the mechanical properties are within the specific range required by the connector, such as the yield strength Rp. 0.2 410~480MPa, tensile strength R m It is 650-800MPa, and the elongation A is greater than 46%. DETAILED DESCRIPTION
[0036] The following examples further describe the present invention in detail.
[0037] Embodiment 1:
[0038] The method for preparing austenitic stainless steel in this embodiment comprises the following steps in sequence:
[0039] 1) Smelting: The electric furnace and AOD furnace smelt the corresponding components in Table 1 below into molten steel, and pour the molten steel into the baked ladle, and then hoist it to the refining station for refining. During the refining, microalloying is performed to ensure that the composition meets Md 30<0 and δ<2, and feed boron wire and silicon calcium wire, soft stirring and calming for 15 minutes to ensure that the molten steel composition meets the above requirements, and then obtain slabs or billets through continuous casting;
[0040] 2) Hot rolling and annealing: hot rolling the slab or billet in step 1) to a target thickness of 2 mm, followed by water cooling, annealing at 1080° C., and pickling to a white skin state;
[0041] 3) Cold rolling: The product of step 2) is cold rolled; specifically, it is cold rolled for 7 passes with a 50% reduction to a thickness of 1.0 mm;
[0042] 4) Annealing and pickling: Anneal the product after step 3) and pickle to remove the surface oxide scale. The specific annealing temperature is 1060℃;
[0043] 5) The product of step 4) is flattened and rolled to obtain a flat steel plate, wherein the flattening elongation is 3%, and the flattening is performed in 5 passes.
[0044] The properties of the austenitic stainless steel prepared in Example 1 are shown in Table 2.
[0045] Embodiment 2:
[0046] The only difference from the above-mentioned embodiment 1 is that: 1. The chemical composition of the stainless steel is different, as shown in Table 1 below; 2. In step 1), the steel is stirred and calmed for 20 minutes; in step 2), the steel is hot-rolled to a target thickness of 3 mm, and the annealing temperature is 1120° C.;
[0047] Step 3) cold rolling with a reduction of 60% for a total of 9 passes, annealing and pickling after rolling to 1.2 mm;
[0048] In step 4), the annealing temperature is 1070°C;
[0049] The properties of the austenitic stainless steel prepared in Example 2 are shown in Table 2.
[0050] Embodiment 3:
[0051] The only difference from the above-mentioned embodiment 1 is that: 1. The chemical composition of the stainless steel is different, as shown in Table 1 below; 2. In step 1), the steel is stirred and calmed for 18 minutes; in step 2), the target thickness of the steel is hot rolled to 2.5 mm, and the annealing temperature is 1100° C.;
[0052] Step 3) cold rolling with a reduction of 60% for a total of 11 passes, annealing and pickling after rolling to 1.0 mm;
[0053] In step 4), the annealing temperature is 1060°C;
[0054] In step 5), the leveling elongation is 2%, and leveling is performed in 3 passes.
[0055] The properties of the austenitic stainless steel prepared in Example 3 are shown in Table 2.
[0056] Embodiment 4:
[0057] The only difference from the above-mentioned embodiment 1 is that: 1. The chemical composition of the stainless steel is different, as shown in Table 1 below; 2. In step 1), the steel is stirred and calmed for 20 minutes; in step 2), the steel is hot-rolled to a target thickness of 3 mm, and the annealing temperature is 1120° C.;
[0058] Step 3) cold rolling with a reduction of 68% for a total of 9 passes, annealing and pickling after rolling to 1.0 mm;
[0059] In step 4), the annealing temperature is 1070°C;
[0060] In step 5), the leveling elongation is 2%, and the leveling is performed in 5 passes.
[0061] The properties of the austenitic stainless steel prepared in Example 4 are shown in Table 2.
[0062] Embodiment 5:
[0063] The only difference from the above-mentioned embodiment 1 is that: 1. The chemical composition of the stainless steel is different, as shown in Table 1 below; 2. In step 1), the steel is stirred and calmed for 15 minutes; in step 2), the target thickness of the steel is hot rolled to 3.5 mm, and the annealing temperature is 1120° C.;
[0064] Step 3) cold rolling with a reduction of 50% for a total of 11 passes, annealing and pickling after rolling to 1.0 mm;
[0065] In step 4), the annealing temperature is 1065°C;
[0066] In step 5), the leveling elongation is 3%, and leveling is performed in 3 passes.
[0067] The properties of the austenitic stainless steel prepared in Example 5 are shown in Table 2.
[0068] Example 6
[0069] The only difference from the above-mentioned Example 1 is: 1. The chemical composition of the stainless steel is different, Cr is 17.0, Ni is 6.0%, Cu is 3.0%, N is 0.25%, Ni is 6.0%, Si is 0.8%, Creq is 18.15%, Nieq is 13.2%, δ is 0.3%, and in step 5), the flattening elongation is 4%, and the flattening is performed in 3 passes.
[0070] Table 1 Chemical composition of the examples (mass percentage %)
[0071]
[0072] The above Creq=%Cr+1.5*%Si+%Mo; Nieq=%Ni+30*(%C+%N)+0.5*%Mn;
[0073] Md 30 (℃)=551-462(%C+%N)-9.2*%Si-8.1*%Mn-13.7*%Cr-29*%Ni-18.5*%Mo-29*%Cu;
[0074] δ=((%Cr+%Mo+1.5*%Si+18) / (Ni+30*(%C+%N)+0.5*%Mn+36)-0.738)*166.7.
[0075] Table 2 Mechanical properties of the examples
[0076] Yield strength(MPa) Tensile strength(MPa) Elongation(%) Example 1 410 670 49 Example 2 420 675 48 Example 3 425 700 46 Example 4 430 695 47 Example 5 415 680 48
[0077] From Table 1 above, we can see that Creq≥18%, Nieq≥12%, Md 30 <0,0<δ<3%.
[0078] It can be seen from Table 2 above that the yield strength of the austenitic stainless steel prepared by the present invention is 410-430 MPa, the tensile strength is 670-700 MPa, and the elongation is 46-49%. The austenitic stainless steel prepared by the present invention satisfies both high yield strength and high tensile strength while ensuring that the elongation is above 46%.
Claims
1. An austenitic stainless steel for a connector, characterized in that: According to mass percentage, it includes the following components: C: 0.04-0.06%, Si: ≤0.7%, Mn: 3.0-4.0%, Cr: 17.0-18.0%, Ni: 5.0-6.0%, N: 0.15-0.25%, Cu: 2.0-2.5%, Mo: 0.2-0.6%, P: ≤0.040%, S: ≤0.030%, and the rest are Fe and unavoidable impurity elements, and at the same time satisfy Creq≥18%, Nieq≥12%, Md 30 <0 and high temperature ferrite content δ: 0<δ≤3%, wherein Creq=%Cr+1.5*%Si+%Mo, Nieq=%Ni+30*(%C+%N)+0.5*%Mn, Md30(℃)=551-462(%C+%N)-9.2*%Si-8.1*%Mn-13.7*%Cr-29*%Ni-18.5*%Mo-29*%Cu; δ=((%Cr+%Mo+1.5*%Si+18) / (Ni+30*(%C+%N)+0.5*%Mn+36)-0.738)*166.7; the yield strength of the austenitic stainless steel is 410~480MPa, the tensile strength is 650~800MPa, and the elongation is greater than 40%.
2. The austenitic stainless steel for a connector according to claim 1, characterized in that: The austenitic stainless steel has a yield strength of 410-430 MPa, a tensile strength of 670-700 MPa, and an elongation of 46-49%.
3. A method for preparing austenitic stainless steel for a connector according to any one of claims 1 to 2, characterized in that: The following steps are included in sequence: 1) Smelting: The molten steel is smelted into molten steel in a furnace according to the above-mentioned composition ratio, and then the smelted molten steel is poured into a baked ladle and hoisted to a refining station for refining. During refining, microalloying is performed to ensure that the composition meets Md30<0 and δ<2, and then boron wire and silicon-calcium wire are fed to ensure that the composition of the molten steel meets the above-mentioned requirements, and then slabs or billets are obtained through continuous casting; 2) hot rolling and annealing: hot rolling and annealing the slab or billet in step 1); 3) Cold rolling: cold rolling the product of step 2); 4) Annealing and pickling: The cold rolled product is annealed and pickled to remove the surface oxide scale.
4. The preparation method according to claim 3, characterized in that: After step 4), leveling rolling is performed to obtain a flat steel plate.
5. The preparation method according to claim 4, characterized in that: The elongation of flattening is 2% to 4%, which is carried out in 3 to 11 passes.
6. The preparation method according to claim 3, characterized in that: In step 1), the boron wire and calcium silicon wire are fed to ensure that the sedation time of soft stirring is ≥ 15 minutes.
7. The preparation method according to claim 3, characterized in that: In step 2), the target thickness after hot rolling is 2 mm to 3.5 mm, and the annealing temperature is 1080°C to 1120°C.
8. The preparation method according to claim 3, characterized in that: In step 3), the total reduction of cold rolling is ≥50%, the reduction of each pass is 8% to 12%, and the target thickness after cold rolling is 1.0 mm to 1.2 mm.
9. The preparation method according to claim 8, characterized in that: In step 4), the annealing temperature is 1060-1070°C.
Citation Information
Patent Citations
Corrosion resistant lean austenitic stainless steel
CN101903549A
Corrosion resistant lean austenitic stainless steel
CN101903549B
Lean austenitic stainless steel
CN102695815A
A high-strength, nitrogen-containing, economical austenitic stainless steel and its manufacturing method
CN109837470B
Austenitic stainless steel
CN109913747A